1995
DOI: 10.1002/elps.11501601310
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping of human deoxyribonuclease I polymorphism by the polymerase chain reaction

Abstract: We recently completely elucidated the molecular basis of genetic polymorphism in human deoxyribonuclease I and found it to be controlled by four codominant alleles, DNASE1*1, *2, *3 and *4. In this paper we describe a novel DNase I-genotyping system that could be used directly on DNA samples using the polymerase chain reaction (PCR) based on the three nucleotide substitutions underlying the protein polymorphism. The system consists of three independent reactions. Since the substitutions neither suppress nor cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 16 publications
2
27
0
1
Order By: Relevance
“…Typing of DNase I protein in urine samples was performed using this improved method for 1,212 unrelated Japanese, a population considerably larger than that in our previous survey (n = 298) [2], Next, DNA samples collected from unre lated Germans and commercially available samples derived from African Americans were subjected to DNase I genotyping by PCR in order to investigate possible differences in the distribution between the different popula tions. It was previously confirmed that a per fect correlation was found between the results of this genotyping method and those obtained by phenotyping using the IEF analysis [ 10], The results are summarized in table l. Seven phenotypes including four rare types were found in Japanese population, whereas in the Germans there were three common types; no other rare types could be detected owing to the small test samples in the latter population.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…Typing of DNase I protein in urine samples was performed using this improved method for 1,212 unrelated Japanese, a population considerably larger than that in our previous survey (n = 298) [2], Next, DNA samples collected from unre lated Germans and commercially available samples derived from African Americans were subjected to DNase I genotyping by PCR in order to investigate possible differences in the distribution between the different popula tions. It was previously confirmed that a per fect correlation was found between the results of this genotyping method and those obtained by phenotyping using the IEF analysis [ 10], The results are summarized in table l. Seven phenotypes including four rare types were found in Japanese population, whereas in the Germans there were three common types; no other rare types could be detected owing to the small test samples in the latter population.…”
Section: Resultssupporting
confidence: 55%
“…Since only DNA samples were obtained from the German and African American populations, genotyping assay for detection of DNase 1 polymorphism from the DNA samples was carried out according to a pre viously described system [10] involving three indepen dent PCRs.…”
Section: Aterials and M Ethodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we modified the PCR amplification strategy to allow the creation of a novel RFLP during the in vitro amplification of target DNA sequences. This method operates by incorporating a deliberate 16 The T195C and A238G substitution sites in ANG created Apa I and HindIII recognition sites, respectively. A 195 bp DNA fragment containing the substitution sites at positions 195 and 238 was amplified by PCR using a set of AGNþ104 and mismatched AGN-298m primers as shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, all three SNPs were analyzed by polymerase chain reaction (PCR) followed by restriction fragment length polymorphism (RFLP) analysis [15,16]. Since the substitution sites corresponding to two SNPs (rs1042725 and rs7968682) neither suppressed nor created any known restriction enzyme recognition sites, we used a mismatched PCR-amplification method for genotyping [17].…”
Section: Snp Typingmentioning
confidence: 99%